Pengaruh Profitabilitas, Ukuran Perusahaan, Likuiditas, dan Risk Minimization Terhadap Pengungkapan Corporate Social Responsibility - Kurniawan, Komang Angga; Yuniarta, Gede Adi (Jurnal Akuntansi Profesi, 2020)
This study aimed at examining the effect of profitability, firm size, liquidity, and risk minimization to reveal corporate social responsibility in property and real estate companies listed on the BEI for the period 2015-2018. The research design used in this study was quantitative research. The population in this study was all of property and real estate companies listed on the BEI for the period 2015-2018 and the sample was taken by using purposive sampling that selected with the criteria that had been determined. This study uses secondary data, namely the annual report of property and real estate companies listed on the BEI for the period 2015-2018. This study uses multiple linear regression analysis techniques with the help of SPSS. The result of the data analysis showed that (1) profitability has no effect on the company CSR, (2) firm size has no effect on the company CSR, (3) liquidity also has no effect on the company CSR, and (4) risk minimization has no effect on the company CSR. It was proven by the result of the t-test that showed the value of the tob was lower than the tcv. The value of the tob of profitability, firm size, liquidity, and risk minimization were – 0, 031, – 0, 048, – 0, 013, and – 1, 611 while the value of the tcv was 1,984 (α = 0.05).